Cowley Papers, - Cowley, H. T. (Henry Thomas), 1837-1917
Correspondence (transcripts) from H. T. Cowley to the Spaldings from 1871 to 1876, concerning missionary work. The first letter is written from Cowley's home in New York and the correspondence continues as Cowley moved from Portland to Kamia on the Nez Perce reservation and finally to Spokane Falls. Also included are some handwritten reminiscences by Cowley and a "recollection" which was actually written by his daughter, Edith Cowley Stillman.